Potential of a nurse telephone triage line to direct elderly to appropriate health care settings - Jacome, Marta (2019)
Aim: To explore the potential of a nurse health triage telephone line to advise and guide elderly users' decisions regarding the appropriate health care setting and self-care. Background: Ageing is a concern in many countries and poses challenges to health care services. Triage and advice lines can play an important role for the (re)organisation of health care delivery. Discussion has been focused on the capacity of these lines to reduce inappropriate demand for acute and emergency departments. Methods: Cross-sectional descriptive analysis. Results: Nurses directed elders to a health care service both by downgrading their initial intentions (concurring to the most common objective) and by upgrading them (e.g., directing elders that intended to stay at home to acute and emergency care). The intention to comply with the nurse's disposition was high. Conclusions: The line helped to improve the appropriateness of acute and emergency care demand and to reduce the overall demand for care by elders. There is nonetheless space for improvement given the underuse of the line by elders. Implications for Nursing Management Health telephone-based triage and advice should be promoted to increase the match between the needs of elderly patients and health resources, thus improving health equity.